Content, methodology and results of the study on the formation of readiness to future border guard officers to apply risk analysis methods - Olena Pshenychna; Oleksandr Didenko; Maria Oliynyk (Association of Social and Educational Innovation, 2019)
The article reveals the content, methods and results of the study of the formation of readiness to future border guard officers to apply risk analysis methods. The essence of readiness for application of methods of risk analysis in operational and service activity, criteria and indicators are defined, levels and state of the formation are characterized. For effective formation of readiness of future frontier officers to apply risk analysis methods, pedagogical conditions have been substantiated and tested experimentally. Based on the research results, methodological recommendations have been developed for cadets, scientific and pedagogical staff.